Utilization of E-Commerce And Aspects of Legal In Business Activities In The Village Prasung, District Buduran, Sidoarjo Regency. - Aldira Mara Ditta Caesar Purwanto; Rohmatul Faizah (Veteran Society : Jurnal Pengabdian Masyarakat, 2020)
The development of today's technology allows people to access all kinds of activities such as communication networks, online applications, transportation online, paying with a digital wallet, online banking transactions and etcetera. Prasung Village in Buduran Subdistrict, Sidoarjo Regency is one of the villages that has the potential to improve the economy of its citizens by utilizing the development of this technology as a forum for promoting the business activities of its citizens. The potential is honed by the existence of community service activities under the title Utilization of E-Commerce And Its Legal Aspects In Business Activities carried out with three stages namely the licensing stage, the socialization stage and the evaluation stage. Then use three methods in delivering the material, namely lecture method, discussion method and question and answer method. The purpose of this community service activity is to improve the economy of citizens by utilizing e-commerce as a means of promoting business activities in the Village of Prasung. Besides providing legal knowledge related to e-commerce as a form of preventive measures to avoid legal problems that might arise from activities in cyberspace. The results obtained from the implementation of community service, namely the delivery of this material can increase motivation for rural communities to be able to use e-commerce so that business activities in the village can be known to the wider community so that it impacts on improving the economy of Prasung Village residents. Keywords : E-Commerce, Technology, Business Activities, Prasung Village